Progesterone treatment of spinal cord injury: effects on receptors, neurotrophins and myelination - de Nicola, Alejandro Federico (2006)
In addition to its traditional role in reproduction, progesterone (PROG) has demonstrated neuroprotective and promyelinating effects in lesions of the peripheral and central nervous systems, including the spinal cord. The latter is a target of PROG, as nuclear receptors, as well as membrane receptors, are expressed by neurons and/or glial cells. When spinal cord injury (SCI) is produced at the thoracic level, several genes become sensitive to PROG in the region caudal to the lesion site. Although the cellular machinery implicated in PROG neuroprotection is only emerging, neurotrophins, their receptors, and signaling cascades might be part of the molecules involved in this process. In rats with SCI, a 3-d course of PROG treatment increased the mRNA of brain-derived neurotrophic factor (BDNF) and BDNF immunoreactivity in perikaryon and processes of motoneurons, whereas chromatolysis was strongly prevented. The increased expression of BDNF correlated with increased immunoreactivity for the BDNF receptor TrkB and for phosphorylated cAMP-responsive element binding in motoneurons. In the same SCI model, PROG restored myelination, according to measurements of myelin basic protein (MBP) and mRNA levels, and further increased the density of NG2+-positive oligodendrocyte progenitors. These cells might be involved in remyelination of the lesioned spinal cord. Interestingly, similarities in the regulation of molecular parameters and some cellular events attributed to PROG and BDNF (i.e., choline acetyltransferase, Na,K-ATPase, MBP, chromatolysis) suggest that BDNF and PROG might share intracellular pathways. Furthermore, PROG-induced BDNF might regulate, in a paracrine or autocrine fashion, the function of neurons and glial cells and prevent the generation of damage.